Applying to B-Schools: Information Sources and Choice Factors - Rani, Malika (Prabandhan: Indian Journal of Management, 2015)
A business school is a university-level institution that confers degrees in business administration. At present, every business school is facing tough times because of cut throat competition in academics. Also, the expectations of students are quite high. While choosing a B-school, the students and parents consider a number of factors. So purpose of this study is to determine the factors which affect the choice of students while applying for admission to B-schools. Also, this study aimed at finding out the major information sources used by students to collect the information related to B-schools. A structured questionnaire was designed to collect the data. A sample of 250 students (including males and females) were drawn from Punjab. Judgmental sampling technique was used to select the sample. To extract the factors, factor analysis technique had been used. Seven factors were extracted based on principal component analysis. It was also found that the main information sources which affected the students' decision of choosing a B-School were : Website of the university, newspapers, the Internet, TV advertisements, billboards/hoardings, word of mouth, and reference groups.